Melatonin Is a Promising Silage Additive: Evidence From Microbiota and Metabolites - Li, Mao; Lv, Renlong; Zhang, Lidong; Zi, Xuejuan; Zhou, Hanlin; Tang, Jun (Frontiers in Microbiology, 2021)
The safe and effective storage of forage are very important. As an important storage method, ensiling can keep fresh forage for a long time with less nutritional loss. Melatonin has antioxidant and bacteriostasis, usually used as a natural preservative. The influence of melatonin on silage microbial or fermentation quality has not been clarified. In the present study, we aimed to clarify whether melatonin affected stylo (Stylosanthes guianensis) silage quality via microbiota and metabolites. Melatonin addition significantly improved the silage fermentation quality, including the increased contents of lactic acid and total acid (244.18–255.81% and 63.95–78.97%, respectively), as well as the decreased in pH and butyric acid content compare with control group. Moreover, 16S rRNA sequencing indicated that melatonin addition enhanced the silage microbial diversity indices (such as increase in Shannon indices but decrease in Simpson indices), and significantly shaped the composition of silage microbiota (such as increased abundances of Pantoea, Stenotrophomonas, Sphingobacterium, and Pseudomonas, and decreased abundance of Weissella). Melatonin addition also dramatically affected the metabolites of sylo silage, such as raised malonic acid and some amino acid metabolism(glycine, threonine, methionine and ornithine), while reduced nucleic acid metabolism(2-deoxyuridine and thymine) and carbon metabolism(allose and 2-deoxy-D-glucose). Collectively, our results confirmed that the lowest melatonin addition (5 mg/kg) could improve the fermentation quality, and the potential mechanisms might be associated with the microbiota and metabolites in stylo.